Synergistic effect of sulphate-reducing bacteria and external tensile stress on the corrosion behaviour of X80 pipeline steel in neutral soil environment. (September 2018) - Xie, Fei; Li, Xue; Wang, Dan; Wu, Ming; Sun, Dongxu
Abstract: X80 pipeline steel, which has a wide application prospect, is easily affected by sulphate-reducing bacteria (SRB) in typical neutral soil and causes stress corrosion cracking. Using a self-made experimental device, the stress corrosion cracking behaviour and mechanism of X80 pipeline steel under the synergistic effects of SRB and tensile stress in Shenyang soil were investigated through the slow strain rate test, electrochemical impedance spectroscopy, potentiodynamic polarisation technology and scanning electron microscopy. In a growth cycle, results showed that SRB quantity initially increased, decreased and peaked on the eight day. SRB improved the stress corrosion cracking sensitivity of X80 steel. When the amount of SRB was 8.7 × 10 3 cell/mL to 1.6 × 10 4 cell/mL, ductile fracture occurred in X80 steel, and mechanical factors could accelerate different forms of anodic dissolution induced by different amounts of SRB. When the SRB quantity increased by 1.7 × 10 4 cell/mL, brittle fracture occurred in X80 steel. The fracture mechanisms were anodic dissolution and hydrogen-induced cracking. Highlights: The synergistic effect of sulfate-reducing bacteria and tensile stress on corrosion behaviour of X80 steel was investigated. The presence of sulfate-reducing bacteria in neutral soil increases the stress corrosion cracking sensitivity of X80 steel. The fracture type and cracking mechanism of X80 steel vary with various quantities of Sulfate-Reducing Bacteria. Whether the X80 steel is subject to stress corrosion cracking is affected by the number of sulfate-reducing bacteria.